The importance of geography in understanding the nature, size and trends of poverty experienced in rural and island communities in Scotland. - Stevelink, Sharon; Wilson, Graeme (International Journal of Population Data Science, 2025)
Objectives Tackling poverty in all its forms is a key priority for the Scottish Government. However, advances in our understanding of how poverty in Scotland is patterned by its diverse geography is hampered by a lack of robust data at a local area level. Methods A systematic data mapping exercise was undertaken to identify suitable datasets with data on a range of poverty outcomes and related proxies, as well as geography indicators. Six datasets were taken forward for descriptive analyses. These included the Households Below Average Income, Children in Low Income Families, Scottish Household Survey, Scottish House Condition Survey, Pupil Census and Understanding Society datasets. Results Relative and absolute poverty rates have increased over time in rural areas but remained relatively stable in urban areas at a higher level. In 2023, one in eight children lived in absolute low income families in islands and remote areas compared to one in five in larger cities. Despite this, among children in relative low income households, nearly three in four residing in islands and remote areas live in working families compared to three in five in larger cities. Households in remote rural areas continued to be the most at risk of experiencing fuel poverty and were more likely to report difficulties affording transport costs compared to those in urban areas. Conclusion The experience of poverty is different, and has changed in different ways, across different types of rural areas in Scotland. Place-based approaches offer the opportunity to tailor policy interventions to some of the observed localised poverty patterns.